Effects of environmental factors on the morphometric characteristics of cultivated lettuce (lactuca sativa l.) (2012)
We evaluated the phenotypic response of three varieties of lettuce Batavia Colwart, Lisa Elisa and Crespa Verde Cassabella in three growing environments: plastic greenhouse, glass greenhouse and open field on the Bogota Plateau (Chia, Cundinamarca), in order to generate useful information to improve the quality of plants grown by farmers, ensuring a healthy product with characteristics that meet market demands. The three agroecosystems were constantly monitored for the environmental variables of temperature, relative humidity and solar radiation; which showed a significant variation between the three agroecosystems. To assess the phenotypic response, we examined the effect of the environmental variables mentioned on seven morphometric variables of agronomic interest. The study showed that, for the variables germination percentage and fresh weight, the environmental effect reached a variance percentage of 79 and 44%, respectively. On the contrary, it was established that the average phenotypic response of the variables clean weight and percentage of dry mass corresponds especially to the effect of genetic varieties with a variance percentage of 35 and 45%, respectively. Similarly, for the variables specific leaf area and total leaf area, it was established that both the effects of environmental and genetic variables explain 87% (50 genetic, 37 environmental) and 56% (31 genetic, 25 environmental), respectively, of the total variability observed.